Faktor-faktor yang berhubungan dengan pemilihan Kontrasepsi IUD di Wilayah Kerja Puskesmas Betung Tahun 2023 - Sulastri, Sulastri; Ciselia, Dewi; Emawati, Wahyu; Dessmansyah, Dessmansyah (NHM PRESS, 2024)
The 2020 World Health Organization (WHO) data shows that the usage of Intrauterine Device (IUD) contraception worldwide, especially in developing countries, is still lower than other contraceptive methods such as injections, pills, condoms, and implants. Factors influencing contraceptive use include maternal attitude towards IUD, knowledge level, and family planning services (implants). Maternal knowledge level, attitude, husband’s support, and family planning services significantly impact the use of contraceptive implants compared to IUDs. The aim of this study is to determine the simultaneous relationship between knowledge, attitude, and family support with the selection of IUD contraception in the working area of Betung Community Health Center in the year 2023. This research employed descriptive analytics with a cross-sectional approach. The population of the study consists of all reproductive-aged women who are family planning acceptors visiting Betung Community Health Center, totaling 287 individuals. The research samples were obtained through purposive sampling, resulting in a sample size of 167 respondents. Data were gathered by means of questionnaires and analyzed using univariate and bivariate analyses, including the chi-square test. The results of this study showed that there was a relationship between knowledge (p value = 0.000), attitude (p value = 0.019), and spousal support (p value = 0.006) with the selection of IUD contraception in the working area of Betung Community Health Center in the year 2023. It is expected that the health center will enhance health promotion efforts, particularly in family planning awareness campaigns, to expand the understanding of reproductive-aged couples regarding contraceptive methods and to provide comprehensive and accurate information regularly, disseminating family planning information consistently.